Biocontrol agents in combination with Moringa oleifera extract for integrated control of Sclerotiumcaused cowpea dampingoff and stem rot - Adandonon, A.; Aveling, T.A; Labuschagne, N.; Tamo, Manuele (Springer, 2006)
Damping-off and stem rot disease-causing Sclerotium rolfsii has been reported as a destructive soil-borne pathogen of numerous crops, especially in the tropics and subtropics. Trials were conducted to test the efficacy of biocontrol agents alone or combined with Moringa oleifera leaf extracts for the control of the disease. In the laboratory, PDA was amended with Moringa leaf extract, and mycelial growth of S. rolfsii was measured. In the greenhouse and field, Trichoderma Kd 63, Trichoderma IITA 508 and Bacillus subtilis were evaluated as seed treatments, soil drench or sprinkle, separately or combined with Moringa leaf extracts. Percentage disease incidence, severity and control were recorded. In the laboratory, the higher the extract concentration the less the mycelial growth and no mycelial growth occurred on extract at 15 or 20 g leaves 10 ml−1 water. In the greenhouse, the highest disease control was observed at a Moringa extract concentration of 15 kg leaves 10 l−1 water (w/v). Seed treatments using Trichoderma Kd 63, and soil sprinkle using Trichoderma IITA 508 had a significantly (P = 0.05) higher effect on a disease incidence than Bacillus. Disease severity followed the same pattern. Moringa seed treatment combined with Trichoderma soil sprinkle resulted in significantly more than 94% and 70% disease control in the greenhouse and field, respectively, with significant yield increase in the field. This is the first report of Moringa leaf extract combined with Trichoderma as an integrated control for Sclerotium damping-off and stem rot of cowpea in the field.